Regional political climate’s moderating role in the association between political conservatism and COVID-19 vaccine hesitancy in the United States - Rachel E. Dinero; William B. Monti; Brittany L. Kmush (PLoS ONE, 2026)
There is an emerging body of evidence linking political conservatism and conservative political climate in the United States to COVID-19 vaccine hesitancy and uptake. The goal of the present research was to examine how political climate moderates the relationship between self-reported political conservatism and COVID-19 vaccine hesitancy and uptake. We collected online survey data from 683 participants between March 8 and April 19, 2023. Controlling for age, education, income, and race, there was an interaction between political conservatism and conservative political climate for both vaccine and booster hesitancy ( β = .07, p = .03; β = .12, p < .001, respectively), such that liberals were less likely to be hesitant regardless of political climate. However, conservatives living in liberal political climates were less vaccine hesitant than their conservative counterparts living in conservative regions. A similar interaction was for the likelihood of receiving a COVID-19 booster (OR =.84, p = .049). Liberals were more likely to receive a booster regardless of political climate, while conservatives’ likelihood was associated with their political climate. Observed patterns linking liberal political climates with vaccine uptake among conservative individuals have important implications for vaccination efforts among conservative individuals in the United States.